Development and initial validation of a palliative care readiness (PALCARE) tool for older adults with cancer: Study protocol - Jyotsana Parajuli; Zhuo Job Chen; Regine M. Smith; Liliana M. Hernandez; Savannah Norris; Sarah Rutledge; Grant Williams; Marie Bakitas; Simon Hsiang (PLoS ONE, 2025)
Introduction Early palliative care (PC) has been recommended for older adults with cancer to address their cancer and treatment related high symptom burden and unmet needs. However, it is underutilized; older adults with cancer are 60% less likely to use PC compared to their younger counterparts. One approach to reduce existing barriers and improve utilization is to assess their readiness for PC. However, there are no gold-standard tools to measure older adults with cancer PC readiness. Methods Informed by the 8 domains of PC recommended by National Consensus Project guidelines, Readiness to Change Framework, and principles of community engaged research, we will use a mixed methods approach, to develop and validate a Palliative Care Readiness (PALCARE) Tool through the following steps: 1) Identify items using semi-structured interviews with 20 diverse (race/ethnicity, rural/urban residence, cancer types) older adults with cancer; 2) Develop draft tool via expert panel surveys followed by focus group with PC experts, and 3) Determine item clarity and wording via cognitive interviews with 20 dyads of older adults with cancer and their family caregivers. Discussion/Conclusion The PALCARE tool will be one of the first measures of PC readiness among a diverse sample of older adults with cancer. Once validated, PALCARE can enhance clinical practice by identifying those who are/are not ready for PC, providing targeted PC that is congruent with their readiness, and educating and supporting those who report being not yet ready for PC. The ultimate goal of this study is to improve PC early access and older adults’ quality of life.